Achieving Smart Resource Management for Better Disaster Management using Space-based Technology in Lowershire Basin, Malawi - Chilonga, Donnex (My University, 2015)
Advancements in new geo-spatial technologies across the globe are seen as a way to advance the decision-making process of first responders before and after a disaster. Unstructured disaster information and an infrastructure for accurate disaster information may be accessed and retrieved successfully through present new and important tools. Such tools could help improve the performance of disaster prediction in any country across the world. This paper illustrates a method based on incorporation of space and terrestrial technologies that aims at providing vital information to first responders for smart management of floods in Loweshire Basin, Malawi.
Keywords: Lower Shire Basin; Mtayamoyo; Geo-spatial technologies; GlobalPositioning System (GPS); Geographic information system (GIS); Flood control; Malawi